Renewable hydrogen production by catalytic steam reforming of ethanol - Kumar, Ashutosh (IIT BHU, 2018)
This thesis work is based on heterogeneous catalyst synthesis and their application in ESR for hydrogen generation. The work was focused on non noble metal Ni and Co based catalyst. The deactivation of catalyst, reformulation of catalyst from the deactivated mixture and pre-treatment reaction effects were also studied. The best possible bimetallic catalyst with support were synthesized by novel route and optimized for ESR reaction. The entire work has been divided into nine chapters and their brief description was stated as follows: Chapter 1 It covers the brief description of hydrogen energy scenario and the complete literature survey on catalytic steam reforming of ethanol. On the basis of it the research objectives were fixed. Chapter 2 In this chapter the different methods opted for catalyst synthesis and the characterization techniques used for observation of physic-chemical properties were briefly described. The schematic diagram and photograph of the complete set up were marked with constituent part and described with their significant role in the ESR reactions. Chapter 3 In this part, active non noble metal Co, Ni and their bimetallic spinel (NiCo2O4) were studied for ESR performance. The NiCo2O4 catalyst has shown completion of ethanol conversion with higher hydrogen selectivity (62%) comparative to Ni and Co at 773K. Chapter 4 In this study, ESR was studied over barren Co metal (Co0 ) from oxalate precursor without any pre-reduction to find out its role in hydrogen and carbon nanofilament generation. The ethanol conversion was found to be 100% with 96.5% hydrogen Department Of Chemistry IIT (BHU) 2 selectivity at 723K. The SEM with EDS analysis revealed that Co0 state was found in between the carbon nanofilament as well as at the tip of carbon nanofilament. Chapter 5 The Co3O4-LaCoO3 catalyst was synthesized from prepared Co-C nanofilament obtained by performing ethanol steam reforming over Co0 . The purpose of the work was to make it cost effective by waste utilization for catalyst synthesis, reutilization of catalyst and the role of composite (Co3O4-LaCoO3) during ESR performance. The ESR performance of Ni/Co3O4-LaCoO3 was found better as compared to Co/Co3O4-LaCoO3 and Co3O4-LaCoO3. It was shown complete ethanol conversion at temperature 823K with 80% hydrogen selectivity. Chapter 6 To elucidate the role of Ni and Co with ZSM-5 support ethanol steam reforming (ESR) were performed. It had shown complete ethanol conversion at 773K but the selectivity in hydrogen generation was found higher for Ni/ZSM-5 catalyst as compared to Co/ZSM-5. The Ni/ZSM-5 catalyst has about 72 % hydrogen selectivity at temperature 873K. Nevertheless, the Ni/ZSM-5 catalyst had shown its stability for high temperature (873K) ethanol steam reforming performance. Chapter 7 In this study, the pre-treatment effect of reduction and redox reaction on Co/CeO2 nano-cube are studied for ESR. The study reveals that the morphological properties of catalysts are not affected by the pre-treatment of H2, air with H2, and CO with air but their activities for ESR are considerably different. The Co/CeO2 treated with H2 has similar ethanol conversion with the catalyst treated with redox atmosphere (CO with air) but their H2 selectivity are found different. Chapter 8 In this chapter a significant route of precipitation for nano sized metal oxide synthesis was discovered from their nitrate precursor in the presence of ethanol solvent by solvothermal treatment. The bimetallic Ni-Co/CeO2 based catalysts were synthesized in Department Of Chemistry IIT (BHU) 3 different concentration. The 20%Ni-Co/CeO2 was found optimum for ESR performance. The optimization of different molar ratio of water and ethanol were also optimized on 20%Ni-Co/CeO2. Chapter 9 It includes the conclusion of whole work performed for different catalyst and operative conditions. The scientific contributions of the work in the area of ESR were also briefly marked. The recommendation for further study in this area was also described
Keywords: hydrogen; catalytic steam; reforming of ethanol